Determinantes da infestação domiciliar pelos Aedes aegypti na cidade de Fortaleza - Bezerra, Haroldo Sérgio da Silva (1999)
The A. aegypti is undoubtedly the most studied mosquito species in the World. This is due to the important role that this mosquito plays in the transmission of Dengue, in its diverse forms, and Urban Yellow Fever. However, despite of all data present in the literature about this species, important questions concerning its biology and ecology are not completely answered. The aim of the present work was to evaluate the environmental factors that are important to the infestation with A. aegypti. To do this we carried out a case-control study in 550 houses located in the "Jardim Iracema" neighbourhood, Fortaleza, Ceará. This neighbourhood was chosen to be our study area due to the high rates of infestation with A. aegypti that its has been having. For this study we selected 275 houses for the case group and 275 for the control group. The case houses were defined as houses with at least one container with immature forms of A. aegypti. The control houses were the ones without infestation. Among the variables, related to the containers found in the houses, that were analysed in this study we highlight the most important ones: the volume of the containers, the high, the cleaning frequency, the position of the container related to the domestic and peridomestic sites, the presence of algae and the relation between the diameter of the mouth and the body of the container. These variables demonstrated to be statistically significant. Regarding the material that the containers were made, the most important ones were made by concrete and masonry. The most important risk factor for infestation with A. aegypti were: the volume of the containers, the cleanness of the water and the relation between the diameter of the mouth and the body of the container. Another risk factors were: the presence of containers in the peridomestic area, the fact that the water stored in the container was not for human consumption and presented algae. The use of the public system of water supply, due to its unreliability, was also a risk factor. In the other hand, the high and the cleaning frequency seem to be protection factors.